Role Consortium Microbial in Decomposition Compound Organic Complex in Wastewater Domestic: Literature Review - Ananta, Yorasakhi; Fitri, Salsabila Dwi (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2025)
The role of microbial consortium and complex organic compounds on domestic wastewater treatment efficiency is a scientific article within the scope of environmental engineering using a biological approach. The purpose of this article is to build hypotheses on the influence of both variables, which will be used in further research. The research objects are obtained from online libraries such as Google Scholar, Mendeley, and other open-access academic platforms. The method used is library research with descriptive qualitative analysis. The results of this article are microbial consortium has an effect on the biodegradation of complex organic compounds in domestic wastewater and the characteristics of complex organic compounds affect the degradation efficiency by microorganisms.